PERAN KOMISI PEMILIHAN UMUM PROVINSI DKI JAKARTA DALAM MENINGKATKAN PARTISIPASI POLITIK MASYARAKAT DALAM PILKADA JAKARTA 2017: Faiz Aprila Fiscana - admin, admin; Hariz Hamdallah, Muhammad Andika (Reformasi Hukum, 2019)
The General Election Commission of the Special Capital Province of Jakarta is the organizer of the General Election which teaches the public how to be involved in the political decision-making process by voting for certain political parties of their choice. The formulation of the problem in this research is the role of the DKI Jakarta Provincial Election Commission in increasing voter participation in the DKI Jakarta elections in 2017. The research objective is to analyze the role of the DKI Jakarta Provincial Election Commission in Increasing Voter Participation in the 2017 DKI Jakarta Election. information to the public the role of the DKI Jakarta Provincial Election Commission. The research method used is normative juridical. The results of the study illustrate the role of the DKI Jakarta Provincial Election Commission in increasing public voter participation in the 2017 DKI Jakarta Regional Election, namely to disseminate information to the public by disseminating information through props such as billboards, posters, pamphlets, pins, banners, stickers on cars / motorbikes / home and through mass media such as radio and newspapers. The conclusion is that the role of the DKI Jakarta Provincial Election Commission is deemed effective enough to have worked hard to increase voter turnout per election event that took place.